Insidensi Infeksi Bayi Baru Lahir Berdasarkan Lama Ketuban Pecah Dini di RSUD Dr. Moewardi Surakarta - Rika Ernawati; Hermawan Udiyanto; Bagus Wicaksono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: The incidence of Premature Rupture of Membranes (PROM) approaches 10% of all delivered which one of the most pregnancy complications. During the latency period of PROM, the bacterias raise inflammation in the vagina, move up in the fetal membranes, umbilical cord, and placenta. Fetal infection caused by aspiration of infected amniotic fluid may lead neonatus stillbirth, preterm delivery, or neonatal sepsis. This study conducted to prove the differences of the incidence in neonatal infection based on the latent period of PROM at Dr. Moewardi Surakarta Hospital. Methods: An observational analytic study with cross sectional method conducted to mother criteria which were term gestation, aged around 20-35 years old, spontaneous vaginal delivery, give birth an infant with a birth weight ? 2500 grams. The independent variable was a latent period of PROM while the dependent variable was a neonatal infection. The subjects were divided into two groups: PROM < 24 hours and PROM ? 24 hours. Further, their neonatal were observed the results of blood culture, leukocyte, neutrophil, thrombocyte, and temperature through medical records. The variable was analyzed by Chi Square test. Results: The subjects were 64 samples in two groups, each consisted of 32 samples. The result of the test stated that the p -value was 0.040 (p < 0.05) with RR = 3.400, thus it could be conclude that there was a statistically significant difference in the incidence of neonatal infection based on the latent period of PROM, where the neonatal at PROM ? 24 hours had opportunity 3.4 times more than the risk of infection of the PROM < 24 hours. Conclusion: There was a statistically significant difference in the incidence of neonatal infection based on the latent period of PROM at Dr. Moewardi Surakarta Hospital. Keywords: Premature Rupture of Membranes, Neonatal infection, Blood culture